WAYS OF DEVELOPING THE MARKET OF RETAIL BANKING SERVICES IN CONDITIONS OF TRANSFORMATION - Son of Rayimnazarov Salokhiddin Davirbek (Journal Park Publishing, 2022)
This article examines the main trends observed in the field of retail banking services, their nature and impact on transformational processes. In addition, a dynamic analysis of the results of the activity of the "Monzo" bank, which specializes in providing retail banking services, was carried out. On the basis of the conducted research, relevant conclusions and proposals were developed.
Keywords: retail banking, trends, dynamic analysis, transformation processes, payments, mobile applications, UnionPay, Discover.